(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The study is an attempt to measure and analyze the interstate tax effort and inefficiency in raising the tax revenues of Indian states over the period, 2005 to 2016. In order to measure the tax effort, Between Effect Panel Data model has been used. Further the tax inefficiency of a particular state has been measured as the distance between tax effort index of this state and the index of benchmark state. Through the course of this study it has been emerged that per capita state domestic product, shares of primary and tertiary sectors are the strong determinants of the tax efforts of state governments. Further the results also demonstrate that the states with low per capita income are more efficient in bridging the gap between their actual and potential tax collections than the states with high per capita income.